Keluarga Pentakostal Sebagai Ekosistem Formasi Iman Anak: Reinterpretasi Pneumatologis Atas Ulangan 6:7 - Pasaribu, George Rudi Hartono; Adriaansz, Rinetje; Siauta, Shirley (JURNAL TABGHA, 2026)
The weakening of the home as the primary context for faith transmission has led many Christian families, including Pentecostal families, to delegate children’s spiritual formation to churches, Sunday schools, or Christian schools. This study aims to reinterpret Deuteronomy 6:7 pneumatologically and to conceptualize the Pentecostal family as an ecosystem of children’s faith formation. It employs a qualitative library-research design and a Pentecostal theological-hermeneutical approach. The primary text is Deuteronomy 6:4–9, with particular attention to the Hebrew verb shanan in verse 7. Secondary data comprise studies of Deuteronomy, Pentecostal theology and hermeneutics, intergenerational faith formation, the sociology of religious transmission. The analysis combines historical-literary and lexical readings, thematic categorization, theological dialogue between the biblical text and Pentecostal spirituality, and conceptual synthesis. The findings demonstrate that shanan denotes more than repetitive verbal teaching; it describes an intensive process by which God’s word is impressed upon children’s memory, affections, character, and practices. The sequence of sitting, walking, lying down, and rising indicates that faith formation permeates the whole rhythm of family life. From a Pentecostal perspective, this formation is pneumatological because it integrates Scripture, the work of the Holy Spirit, prayer, worship, testimony, parental modeling, discernment, and children’s participation. The study’s novelty is the Pentecostal Faith Formation Ecosystem Model, which connects the foundation of Scripture, the formative agency of the Spirit, parental responsibility, the home’s spiritual atmosphere, everyday and digital rhythms, and the outcomes of Christlike character and witness. The model positions the church as a partner that equips parents rather than replaces them.